2022
DOI: 10.1111/vde.13140
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of ciclosporin and oclacitinib on mediators of tolerance, regulatory T‐cells, IL‐10 and TGF‐β, in dogs with atopic dermatitis

Abstract: Background: Atopic dogs often are managed with allergen-specific immunotherapy (AIT) and concurrent dosages of ciclosporin (CSA) or oclacitinib to alleviate their clinical signs. Both drugs might affect proper tolerance induction by inhibiting regulatory T-cell (Treg) induction. Hypothesis/Objectives: We evaluated Treg cell numbers and serum interleukin (IL)-10 and transforming growth factor-beta (TGFβ)1 levels in dogs diagnosed with atopic dermatitis (AD) and successfully treated with either CSA or oclacitini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(165 reference statements)
0
3
0
Order By: Relevance
“…Instead, Herrmann et al. ( 2023 ) did not find any effect of oclacitinib on the percentage of regulatory T cells (CD4 + CD25 + FoxP3 + ), indicating the variation of results found depending on whether the studies are done with peripheral lymphocytes in vivo or after stimulation with antigens with in vitro studies. This observation did not found in our atopic dogs, and no effect of the oclacitinib treatment on lymphocyte population in vivo was detected, probably because the dose was low.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Instead, Herrmann et al. ( 2023 ) did not find any effect of oclacitinib on the percentage of regulatory T cells (CD4 + CD25 + FoxP3 + ), indicating the variation of results found depending on whether the studies are done with peripheral lymphocytes in vivo or after stimulation with antigens with in vitro studies. This observation did not found in our atopic dogs, and no effect of the oclacitinib treatment on lymphocyte population in vivo was detected, probably because the dose was low.…”
Section: Discussionmentioning
confidence: 96%
“… 2016 ; Herrmann et al. 2023 ) in atopic dogs, but in the study by Jasiecka-Mikołajczyk et al. ( 2018 ) demonstrated that oclacitinib had no influence on the expression of CD25 and Foxp3 on CD4 + and CD8 + T cells, but a dramatic loss of CD4 + and CD8 + T cells was caused by oclacitinib when the drug was evaluated in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations of complete blood counts and serum biochemistries for patients on long-term oclacitinib reported mild leukopenia (most commonly neutropenia and rarely lymphopenia). 3,8 Rare reports 10 of changes in the serum biochemistry and urinalysis have been reported but do not often warrant cessation of therapy. In initial studies, 10 symptoms of urinary tract infections were seen in 0.5% to 11.3% of dogs that were on chronic oclacitinib; however, quantitative bacterial cultures were not performed.…”
Section: Adverse Eventsmentioning
confidence: 99%